Usul Fikih dan Metode Pengajarannya di IAIN Sunan Ampel Surabaya - Noor Naemah Abd Rahman (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
Ushul fiqh (Islamic legal theory) as a method can be utilized to analyze various cases and create a dynamic legal solution to them. As a science, ushul fiqh is dynamic, contextual to time space, scholarship development, and the jurists’ competence. Islamic law is highly dependent on ushul fiqh since it is the guide for Islamic jurisprudence as practical solution for daily issues. On that basis, full mastery of ushul fiqh is a requirement of conducting ijtihad (interpretation).As an institution f Islamic learning focusing on Islamic law and jurisprudence, Faculty of Islamic law is expected to pay attention to the teaching of ushul fiqh, both in theory and practice. Thus, the learning of ushul fiqh is directed toward the anatomy of thought and epistemology in the thought of Islamic law with more emphasis on ushul fiqh as an applied science. To achieve a desired result, several supports should be prepared, such as competent lecturers, supportive attitude of lecturers towards students, good quality of curriculum, detailed syllabi and precise teaching plan, effective teaching method and so forth. By doing so, usul fikh will not only become dead science, but also becomes a means to construct the spirit of ijtihad and eradicates the taqlid tradition which have been hampered the scientific development in Islam for long time.